Model pembelajaran berbasis lingkungan untuk meningkatkan kreatifitas guru di SMP Negeri 22 Satu Atap Mubri Kampung Mandopi Rimon, Distrik Manokwari Utara, Kabupaten Manokwari, Provinsi Papua Barat - Simon Towansiba; Hugo Warami; Benidiktus Tanujaya (Program Pascasarjana Universitas Papua, 2022)
The environment around Junior High School Negeri 22 Satu Atap Mubri can be a medium of learning in the teaching and learning process. The use of the environment as a learning medium has a positive impact on increasing student interest in learning. This is because when students study outside the classroom, students are faced with the real situation so that students tend to be active and do not get bored quickly in the learning process. From the surrounding environment, there is also much that can be taught, introduction to ecosystems such as plants and animals. This research uses quantitative and qualitative. The research location at SMP Negeri 22 Satu Atap Mubri North Manokwari District is a case study in that school. The research used the method of field observations, interviews and student ability tests on 28 students who sat in class VIII SMP Negeri 22 Mubri. The results of the pre-test and the final test show an interesting comparison, namely the number of students who scored Very Good (VG) on the pre-test was only two students (7.14%) while in the final test there was an increase where as many as 16 students (57.14%) got The SB value means that the comparison between the pre-test and the final test has a good increase of 50%. Meanwhile, students who scored Good (B) only increased by one (1) point. The results of the pre-test there were 5 students who got good scores while in the final test there were 6 students or an increase of 1 point or from 17.86% increased to 21.43%. Sufficient Value (C) decreased, namely from 10 or 35.71% of students in the pre-test down to 4 students in the final test (14.29%) thus there was a decrease of 6 points. A sharp decrease actually occurred in the Less (K) score, where from 9 (nine) students who scored less on the Pre-Test test at the end of the final test to zero (0%). Meanwhile, for Very Less (K) scores there was no change. namely between the pre-test and the final test as many as 2 students or as much as 7.14%.